Aurelia - Lawhead, Stephen R., 1950- (Lawhead, Stephen R., 1950- Pendragon cycle., 2025)
"Aurelia: Last witness of an elder time, handmaid of the age to come. It was a time of the end of empire. The world was in turmoil. The Romans were abandoning Britain, leaving the remaining servants of empire to try to stem the tide of chaos. Aurelia was one such, the child of a prefect, and wife of another. The entire world had changed around her. How could she raise her sons to thrive in such a world? Everywhere, it seemed, the old, well-ordered realm she had been born into was passing away to be replaced by...what? It was that question her sons, Aurelian and Arthur, with the help of Merlin, were to answer...."--